Analytical modelling and power density optimisation of a single phase dual active bridge for aircraft application - Fritz, Niklas; Rashed, Mohamed; Bozhko, Serhiy; Cuomo, Fabrizio; Wheeler, Pat (2018)
A design procedure for the Dual Active Bridge (DAB) converter is presented, which aims to optimized power density and computational effort. When designing a DAB, the selection of circuit design parameters such as switching frequency, leakage inductance and semiconductor technologies is a complex question when targeting losses and weight minimization of the final design. In this paper, analytical models of the operating waveforms, the losses and the weight of all DAB components are developed. The proposed design algorithm is used for designing a 3kW high frequency DAB for an aircraft DC power system.